Contribution of Other Respiratory Viruses During Influenza Epidemic Activity in Catalonia, Spain, 2008–2020 - Nuria Torner; N. Soldevila; L. Basile; M. M. Mosquera; P. de Molina; M. A. Marcos; A. Martínez; M. Jané; A. Domínguez; The Working Group for the Catalan Influenza and Acute Respiratory Infection Sentinel Surveillance Network (PIDIRAC) (Microorganisms, 2024)
Background: During seasonal influenza activity, circulation of other respiratory viruses (ORVs) may contribute to the increased disease burden that is attributed to influenza without laboratory confirmation. The objective of this study was to characterize and evaluate the magnitude of this contribution over 12 seasons of influenza using the Acute Respiratory Infection Sentinel Surveillance system in Catalonia (PIDIRAC). Methods: A retrospective descriptive study of isolations from respiratory samples obtained by the sentinel surveillance network of physicians was carried out from 2008 to 2020 in Catalonia, Spain. Information was collected on demographic variables (age, sex), influenza vaccination status, epidemic activity weeks each season, and influenza laboratory confirmation. Results: A total of 12,690 samples were collected, with 46% (5831) collected during peak influenza seasonal epidemic activity. In total, 49.6% of the sampled participants were male and 51.1% were aged <15 years. Of these, 73.7% (4298) of samples were positive for at least one respiratory virus; 79.7% (3425 samples) were positive for the influenza virus (IV), with 3067 samples positive for one IV type, 8 samples showing coinfection with two types of IV, and 350 showing coinfection of IV with more than one virus. The distribution of influenza viruses was 64.2% IVA, 35.2% IVB, and 0.1% IVC. Of the other respiratory viruses identified, there was a high proportion of human rhinovirus (32.3%), followed by human adenovirus (24.3%) and respiratory syncytial virus (18; 7%). Four percent were coinfected with two or more viruses other than influenza. The distribution of coinfections with ORVs and influenza by age groups presents a significant difference in proportions for 0–4, 5–14, 15–64 and >64 (21.5%, 10.8%, 8.2% and 7.6%: p < 0.001). A lower ORVs coinfection ratio was observed in the influenza-vaccinated population (11.9% vs. 17.4% OR: 0.64 IC 95% 0.36–1.14). Conclusions: During the weeks of seasonal influenza epidemic activity, other respiratory viruses contribute substantially, either individually or through the coinfection of two or more viruses, to the morbidity attributed to influenza viruses as influenza-like illness (ILI). The contribution of these viruses is especially significant in the pediatric and elderly population. Identifying the epidemiology of most clinically relevant respiratory viruses will aid the development of models of infection and allow for the development of targeted treatments, particularly for populations most vulnerable to respiratory viruses-induced diseases.